PENGARUH TIME BUDGET PRESSURE TERHADAP KUALITAS AUDIT DAN BUDAYA ETIS SEBAGAI VARIABEL MEDIATOR - Valentina Elizabeth; Herry Laksito (Diponegoro Journal of Accounting, 2017)
The goal of this research is to test how time budget pressure affect audit quality by ethical culture and also to test how ethical culture mediate time budget pressure on audit quality. This research uses primary data collected by using questionnaire that shared for auditor in Jakarta. Seventy five samples are used in this research. Data analyzed with the quality data test, classic assumption test and hypothesis testing tools that are used in this research is multiple linear regression, path analysis. From the regression, there are some findings: (1) time budget pressure does have negative impact to the audit quality; (2) time budget pressure does have negative impact to the ethical culture; (3) The ethical culture is found to have positive impact to the audit quality. From these results can be concluded that ethical culture mediates the indirect relationship between time budget pressure on audit quality.